The Mediating Role of Brand Trust in The Relationship Between Brand Authenticity and Brand Loyalty: A survey study on customers of Baghdad Soft Drinks Company - Adil Mahmood Alkhafagi, Yasir (Iraqi Journal for Administrative Sciences, 2024)
This study aims to know the nature of the relationship between the three research variables, which are “brand authenticity”, “brand trust”, and “brand loyalty”. In addition to knowing the role of “brand trust” as a mediating variable in the relationship between “brand authenticity” and “brand loyalty”. These relationships were tested through a survey conducted using an electronic questionnaire published on social media targeting customers of the Baghdad Soft Drinks Company. The number of respondents to the questionnaire was (236) observations. SPSS V.23 and AMOS V.23 programs were used to analyze the data statistically. The study reached a set of conclusions, the most important of which is the positive role of “brand trust” as a mediator in the relationship between “brand authenticity” and “brand loyalty”.